Specific Flavor Compounds Derived from Nelson Sauvin Hop and Synergy of these Compounds: Based on a poster presented at the 32nd Congress of the European Brewery Convention, Hamburg, Germany, May 2009 - Takoi, Kiyoshi; Degueil, Marie; Shinkaruk, Svitlana; Thibon, Cécile; Kurihara, Toshio; Toyoshima, Koichi; Ito, Kazutoshi; Bennetau, Bernard; Dubourdieu, Denis; Tominaga, Takatoshi (BrewingScience, 2009)
Nelson Sauvin (NS) is a unique hop cultivar that gives a specific flavor (exotic fruit-like, Sauvignon Blanc wine-like) to finished beers. We have attempted to identify the specific flavor compounds derived from NS. First, isobutyric esters, including 2-methylbutyl isobutyrate (2MIB), have been found in the beers used with NS (NS product). These compounds had a green apple-like and/or apricot-like flavor. We next focused on certain volatile thiols that are well known to contribute to wine flavors, especially Sauvignon Blanc, and identified two new volatile thiols, 3-sulfanyl-4-methylpentan-1-ol (3S4MP) and 3-sulfanyl-4-methylpentyl acetate (3S4MPA), having a grapefruit-like and/or rhubarb odor, similar to that of Sauvignon Blanc. Among these compounds, 3S4MP was contained twice of its thresholds and 3S4MPA and 2MIB were contained below their threshold, in the NS product. However, it was confirmed that 3S4MP enhanced the flavors of 3S4MPA and 2MIB by synergy. In addition, we also confirmed that 3S4MP enhanced the flavors of terpene alcohols (linalool and geraniol). Therefore, we concluded that 3S4MP might contribute to the specific flavor of the NS product as a key compound having two roles, its own characteristic flavor and its function as a flavor enhancer.